A review of the green economy in Cape Town: local policy in the light of international approaches - Petrik, Marko (Department of Civil Engineering, 2017)
The industrial economy of the last 100 years has resulted in significant externalities, chief of which has been anthropogenic climate change caused by the release of greenhouse gasses into the atmosphere. The green economy is an approach to economic activity that has been developed in an effort to mitigate against this and attempt to shift the world economy onto a more sustainable course. South Africa has a particularly carbon-intense economy, and as such bears a considerable burden to follow this shift. Cape Town, following the lead of national government, has begun to respond to climate change and has made steps to adopt the green economy. However, much of the literature and theory developed around the green economy has been produced by developed nations, which may render it problematic to be adopted by a city in a developing nation, such as Cape Town. This dissertation begins with a brief description of the background and definition of the green economy. Based on a reading of the international literature, it then uses an analytical overview of conceptual descriptions of the green economy to develop a Transition Framework as a tool for evaluation and comparison. The Transition Framework is then applied to the green economy in the city of Cape Town as a case study. While the City of Cape Town quite overtly applies international conceptions of the green economy to its formulation, it was found that there were some significant local deviations: political parties play an important role in leading and shaping the local green economy; there is a particular need to balance green economy interventions against the preservation of municipal income from tax; the city's spatial-geographic character plays an important role in strategy and planning; and the primary aim of the local green economy is to increase economic growth and produce employment opportunities, in order to ensure social and political stability. This study highlighted the fact that international conceptions of the green economy do have a significant amount of flexibility towards local conditions, this may in some cases result in a drift away from some of its stated aims (reducing greenhouse gasses, for example) towards addressing the most pressing local issues. This may potentially render its goals unachieved.